Detection of Leishmania parasites species isolated from patients suffering from Kala-azar using one-step PCR - Ahmad Golkar (فصلنامه دانشگاه علوم پزشکی جهرم, 2011)
Introduction:Visceral leishmaniasis (Kala-azar) is a major parasitic disorder caused by species of Leishmania genus, namely L. donovani and L. infantum. Epidemiologic evidence indicates that visceral leishmaniasis is common in certain regions of Jahrom town in the province of Fars, Iran. The present study was conducted with the aim of identifying the causative agent of visceral leishmaniasis in this town. Material and Methods:This is an experimental study on 16 patients admitted with Kala-azar in Shahid Motahari Hospital, Jahrom, from 1997 to 2004. Bone marrow samples were obtained from patients. DNA was extracted from microscopic slides and specific polymerase chain reaction (PCR) was used to identify the parasite species. For this purpose, a segment of minicircle kinetoplast DNA of the parasite was amplified using LINR4 and LIN17 primers. The products were evaluated by electrophoresis in 1.5% agarose gel.Results:All patients were serologically positive on indirect immunofluorescent assay. On direct examination of bone marrow smears, parasitic amastigotes (Leishman bodies) were observed in large numbers. All specimens produced a 720 base-pair band on PCR. Comparing these bands to the standard species bands identified L. infantum in all our patients.Conclusion:The findings of the present study indicate that using one-step polymerase chain reaction and LINR4 and LIN17 primers is a simple and rapid method for identification of species. Also, the causative agent for visceral leishmaniasis is L. infantum in all our patients.